Hox transcriptomics in Drosophila embryos - Polychronidou, Maria; Lohmann, Ingrid (Hox genes, 2014)
Hox proteins are evolutionarily conserved homeodomain containing transcription factors that specify segment identities along the anteroposterior axis of almost all bilaterian animals. They exert their morphogenetic role by transcriptionally regulating a large battery of downstream target genes. Therefore the dissection of transcriptional networks regulated by Hox proteins is an essential step towards a mechanistic understanding of how these transcription factors coordinate multiple developmental and morphogenetic processes. High-throughput techniques allowing whole-transcriptome mRNA expression profiling are powerful tools for the genome-wide identification of Hox downstream target genes in a variety of experimental settings. Here, we describe how to quantitatively identify Hox downstream genes in Drosophila embryos by performing a Hox transcriptome analysis using microarrays.